ANALISIS EKONOMI PENGGUNAAN PUPUK ORGANIK DALAM USAHATANI DI KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Nugroho, Agung Enggal (Jurnal Magrobis, 2017)
This study aims to calculate the productivity cause the use of organic fertilizers, and the level of income and feasibility of farming, and to determine the potential waste that can be used as organic fertilizer and the cause of the lack of development of organic fertilizer use.The sample in this research is determined by nonprobability sampling that is purposive sampling. Respondents were determined by dividing into three criteria on each cultivated plant, 3 respondents for inorganic criteria, 3 respondents for mixed criteria, and 3 respondents for organic criteria. Total of respondents in this study is 45 respondents.The results showed that the productivity and income of farming by using organic fertilizer is still relatively lower than in the cultivation using inorganic fertilizer. The main factor causing low income from farming with the use of organic fertilizer is due to the market of organic products that are not yet available. Potential waste that is utilized for organic fertilizer in Anggana District is quite abundant, such as from cow dung, buffalo, goat, chicken, and from rice straw. The causes of underdevelopment of organic fertilizers, among others is the long making procces and application period, high indirect production, and unavailable market.Keywords : Organic Fertilizer, Productivity, Farming, Income